Two Strains of Lymnaea stagnalis and the Progeny from Their Mating Display Differential Memory-Forming Ability on Associative Learning Tasks - Sunada, Hiroshi; Totani, Yuki; Nakamura, Ryota; Sakakibara, Manabu; Lukowiak, Ken; Ito, Etsuro (Frontiers in Behavioral Neuroscience, 2017)
The pond snail Lymnaea stagnalis learns and forms long-term memory (LTM) following both operant conditioning of aerial respiratory behavior and classical conditioning of taste aversive behavior. In the present study, we examined whether there are interstrain differences in the ability to form LTM following these two types of conditioning. A strain of Lymnaea (TC1) collected in Alberta, Canada exhibits superior memory-forming ability following aerial respiratory operant conditioning compared to a laboratory-reared strain of Lymnaea from the Netherlands known as the Dutch strain. We asked whether the offspring of the Canadian TC1 and Dutch snails (i.e., filial 1 (F1) cross snails) would have the superior memory ability and found, rather, that their memory ability was average like the Dutch snails. That is, the Canadian TC1 snails have superior ability for LTM formation following aerial respiratory operant conditioning, but the Dutch and the generated F1 cross have average ability for memory forming. We next examined the Canadian TC1, Dutch, and F1 cross snails for their ability to learn and form memory following conditioned taste aversion (CTA). All three populations showed similar associative CTA responses. However, both LTM formation and the ratio of good-to-poor performers in the memory retention test were much better in the Dutch snails than the Canadian TC1 and F1 cross snails. The memory abilities of the Canadian TC1 and F1 cross snails were average. Our present findings, therefore, suggest that snails of different strains have different memory abilities, and the F1 cross snails do not inherit the memory ability from the smart strain. To our knowledge, there have been a limited number of studies examining differences in memory ability among invertebrate strains, with the exception of studies using mutant flies.